Response of young rice panicles to salt stress: insights based on phenotype and transcriptome analysis - Duan, Fanrui; Wu, Fugui; Li, Zhen; Zhang, Kai; Ma, Qilin (Frontiers in Plant Science, 2024)
Saline-alkali soil is one of the most significant environmental factors that restrict thesoils limit rice growth and production scale of rice.. With the continuous increase in the increasing global population, the cultivation of rice crops in saline-alkali soils has become increasingly urgent.Therefore, identifying the molecular regulatory networks and key genes responsible for rice's enhancing rice salt tolerance is crucial for enhancing its stress resistance, expanding the scale of rice production, and increasing improving yields in salinethese areas. This study observedinvestigated the developmental characteristics of young panicles and pollen fertility ofin two rice varieties with different salt tolerance, 58M and 58L, under salt stress conditions. The results. Results showed that the 58M variety had strongermore substantial salt tolerance during the developmental stage of young panicles.panicle development. RNA-seq was performed on sequencing of 18 samples of these twofrom both varieties under high salt treatment for three different durations (0h, 6h, 24h). Through differential expression analysis, it was found that the number of stress (0 h, 6 h, and 24 h) identified 469 common differentially expressed genes (DEGs) within each variety was small, a total of 469 common DEGs was identified. The differences and 2308 DEGs between the varieties were larger, with a total. Kyoto Encyclopedia of 2308 DEGs identified. Genes and Genomes (KEGG) pathway enrichment analysis showed enrichment in highlighted significant pathways such as the biosynthesis of phenylpropanoid compoundsbiosynthesis, protein processing in the endoplasmic reticulum, , and flavonoid biosynthesis of flavonoid compounds, and the biosynthesis of cutin, suberin, and wax, between and within the varieties. By constructing a weighted. Six gene co-expression network, six specific Style Definition: 修订1 modules highly related to rice salt tolerance were identified. By calculating the connectivity and correlation coefficients of genes within the modules,, with six candidate genes (LOC_Os05g38530,